2016
DOI: 10.1134/s1607672916010178
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila polytene chromosome bands formed by gene introns

Abstract: Genetic organization of bands and interbands in polytene chromosomes has long remained a puzzle for geneticists. It has been recently demonstrated that interbands typically correspond to the 5'-ends of house-keeping genes, whereas adjacent loose bands tend to be composed of coding sequences of the genes. In the present work, we made one important step further and mapped two large introns of ubiquitously active genes on the polytene chromosome map. We show that alternative promoter regions of these genes map to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This rule holds true for the organization of the fourth chromosome of Drosophila (Sidorenko et al, 2018). In addition, there are some atypical cases of band and interband genetic organization, with one long gene occupying up to nine cytological structures (Zhimulev et al, 2016;Khoroshko et al, 2019).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…This rule holds true for the organization of the fourth chromosome of Drosophila (Sidorenko et al, 2018). In addition, there are some atypical cases of band and interband genetic organization, with one long gene occupying up to nine cytological structures (Zhimulev et al, 2016;Khoroshko et al, 2019).…”
Section: Resultsmentioning
confidence: 92%
“…To sum up, it has been shown that the banding pattern is a universal principle of both polytene chromosome and diploid cell chromosome organization, and housekeeping genes are embedded in two interphase chromosome structures: their promoters are localized in the interbands, and the structural parts lie in adjacent loose bands (Zhimulev et al, 2014). In addition, it has recently been discovered that long D. melanogaster genes can occupy several morphological structures of polytene chromosomes (Zhimulev et al, 2016;Khoroshko et al, 2019). For example, using fluorescent in situ hybridization (FISH), it was shown that long introns of the ubiquitous active genes dlg1 (~18 kb) and CG43867 (~106 kb), interrupted by short rare exons, form loose gray bands 10В8-9 and 1D1-2, respectively, and their 5′ and 3′ regulatory regions lie in the decompacted interbands of the X chromosome .…”
Section: Atypical Cases Of Gene Localization In the Structures Of Polmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bridges' map [25], two interbands and one grey band, being composed of intron material that is ~36 kb in length, are situated between the two probes ( Figure 14). 3.2.10. dlg1 dlg1 (discs large 1) is located on chromosome X in the 10B6-10B11 region (according to UCSC, Table 1); Zhimulev et al [46] have preliminarily localized it in the 10B8-1011 region. The gene length is 40.1 kb (81.9% of it accrues to introns); 21 transcripts are read from dlg1 (only three are shown in Figure 15D, Table 1).…”
Section: Nrgmentioning
confidence: 99%
“…When compared with the DNA length in the bands, introns up to 400 kb are quite large and, therefore, must somehow be detected at the chromosome level; at least, it can be expected that structures that are based on such long introns can be seen under the light microscope, but such data are unavailable in literature. According to our recently obtained preliminary data, certain large genes can occupy extended sections of chromosomes [45,46]. In the present study, we examined the localization sites of the genes that are mentioned above; in addition to that, we picked 12 new regions and analyzed their gene, intron, and chromatin composition, as well as studied their cytological location.…”
Section: Introductionmentioning
confidence: 95%